Kajian Nilai dan Fungsi Sosial Ruang Publik - Anugrah Amin; Arifuddin Akil; Marly Valenti Patandianan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
Losari Beach cannot be avoided from a variety of social problems which causes the interference of social function of public space as a place for people to interact. Therefore, the study of social function of public space at Losari Beach are needed to make a better place and to improve the quality of Losari Beach as the public space. Spatial analysis (GIS) was conducted to figure the pattern of visitors’ activities and characteristic of public space at Losari Beach. Qualitative descriptive and quantitative analysis were used to find out the types of activities and the indicators of values and social function of Losari Beach. The result was Losari Beach consists of some kinds of public spaces like plazas, pedestrian ways, restaurants, and floating mosques which can be the attractive point. The value and social function indicators such as the comfort and the security, cannot fulfill the people’s needs due to the lack of facilities to support their activity and to feel safe and comfort. Thus, the needs and the democratic was needed to protect the people’s rights and the values were not achieved well.